(untitled) (Journal of Organizational Psychology, 2017)
Conflict management has always been regarded as a major task of business management practice and as a preeminent issue of business management research. In this paper, the authors analyse the outcomes of a laboratory experiment, which was also supposed to validate an empirical field study of real world conflict solution via mediation tools in in-court and out-of-court legal cases, either with the intervention of a mediator or without. The authors conceptualise the theoretical model of “Co-Integrative Mediation (CIM)” as a comprehensive conflict management tool, based on a combination of game theory, behavioural economics, new institutional economics, and social capital theory conjectures. The application of the CIM model against the “classical” approach of conflict solution by decision of a “legitimised” institution was tested via an experimental investigation. As a result, it can be tentatively stated that “CIM” tends to show significantly superior effects concerning the economic and sociopsychological outcomes of the conflict management processes